PERBEDAAN PROFIL LIPID DAN KADAR ASAM URAT PADA PASIEN DIABETES MELITUS TIPE II DENGAN DAN TANPA HIPERTENSI - Filliana Savitri; Intani Kurnia Savitri; Pugud Samodro; Lantip Rujito (Scripta Biologica, 2017)
Diabetes Mellitus type 2 is the 7th world of death problem with the 95% proportion rate. Hypertension has also a correlation with this condition. The mortality of cardiovascular is 2-3 times over from diabetics with hypertension than diabetics with normotension which caused by lipid and aciduric disturbations. This study was conducted using cross-sectional design. Twenty-five sample of diabetics normotension and 25 sample of diabetics patient along with hypertension in Ajibarang Hospital District Banyumas and comply with inclusion-exclusion criteria were taken suing consecutive sampling. Data from the cholesterol and triglyceride total test were collected and analyzed with Mann-Whitney test. Additionally, HDL cholesterol and LDL was analyzed using T-Test.  This Study showed that average total cholesterol from diabetics along with hypertension patients was in a range of 185.16 ± 36.59 and Diabetics patient without hypertension was 196.76 ± 44.62 (p = 0,503). Besides, the average rate of triglyceride level on diabetics patient with hypertension was 181.76 ±72.68 and diabetics patient along without hypertension was 180.28 ± 125.75 (p=0,367). The average rate of HDL cholesterol level on diabetics patient with hypertension was 39.12 ± 11.07 and diabetics patient along without hypertension was 42.37 ± 14.98  (p = 0,387). In addition, Average rate of LDL level on diabetics patient with hypertension was 112.57 ± 24.77 and diabetics patient along without hypertension was 118.33 ± 37.41 (p = 0,524). The average rate of uric acid on diabetics patient with hypertension was  6,120 ± 1,45 and diabetics patient along without hypertension was 5,768 ± 2,45 (p=0,200).  As a conclusion, there is no difference with total cholesterol, triglyceride, HDL, LDL cholesterol, and uric acid significant from diabetics patient with or without hypertension in Ajibarang Hospital District Banyumas in 2016.